Interactive E-Module of Mixture for Improving Students’ Creative Thinking Skills - Devita Ayu Ramadhani; Rini Anggi Arista (PT Ahan Group Publisher, 2026)
This study aims to develop an interactive e-module that is valid and implementable to help improve students' creative thinking skills in Mixture Substance. This developmental study utilises the 4D model from Thiagarajan et al. (1974). This study involved 60 eighth-grade students from a public junior high school in Karangploso, Malang, using a convenience sampling technique and a nonequivalent control group design. Descriptive analysis techniques were used to explain the pretest-posttest results; an independent-samples t-test was used to analyse differences in creative thinking ability between the experimental and control groups; and an N-Gain test was used to determine improvement categories in creative thinking ability. Media and material validation results from expert validators and educators showed agreement, with almost perfect agreement in the categories. The posttest t-test results for both groups showed p-values less than 0.05, indicating a significant difference in creative thinking ability after learning. The experimental group’s N-Gain value was higher than the control group's, at 0.5021, indicating that students improved their creative thinking skills in the moderate category, while the control group achieved only 0.1551 in the low improvement category. Based on these findings, learning mixture materials using interactive e-modules in experimental classes is effective in improving students' creative thinking skills.